Development of co-processed excipients in the design and evaluation of atorvastatin calcium tablets by direct compression method - Pusapati, Ravi Teja; Kumar, MVR Kalyan; Rapeti, Siva Satyanandam; Murthy, TEGK (International Journal of Pharmaceutical Investigation)
Introduction: Co-processed excipients were prepared to improve the process ability and effi cacy of commonly used excipients and to impart multi-functional qualities to the excipients and hence that the tablets with the desired attributes can be produced. In this study, acacia and calcium carbonate (CaCO3) were used to prepare a co-processing excipient suitable for the preparation of atorvastatin calcium tablets. Acacia is used as binder and CaCO3 as fi ller. CaCO3 also acts as alkalizer and thus suitable to improve the dissolution rate of pH dependent soluble drugs like atorvastatin. Materials and Methods: The tablets were prepared by direct compression method and the physical properties of tablets such as hardness, friability and dissolution profi les of tablets were evaluated. Acacia was used in the form of mucilage. Various ratios of the co-processing excipients were formulated by granulation technique and the blend properties were evaluated by their Hausner’s ratio and Carr’s index values. Based on the Kawakita plots, it was found that the formulation with 3% acacia mucilage (0.9 mg acacia and 26.6 mg of CaCO3) showed good fl uidity and the formulations with 4% (1.27 mg of acacia and 26.23 mg of CaCO3) and 5% acacia mucilage (1.62 mg of acacia and 25.88 mg of CaCO3) showed more cohesiveness. The formulations include 1-5% of the acacia mucilage as the binding agent. Results: The granules of formulations with low percentage of acacia mucilage (1% and 2%) failed the test for friability. The granules of the formulations with pure acacia (F1) and pure CaCO3 (F2) showed passable fl ow properties. Conclusion: The formulation with 3% acacia mucilage (F3, 0.9 mg acacia and 26.6 mg of CaCO3) showed least dissolution time (<1 min) and is found as the best formulation among the other formulations containing 4% (F4, 1.27 mg of acacia and 26.23 mg of CaCO3) and 5% (F5, 1.62 mg of acacia and 25.88 mg of CaCO3) acacia mucilage.
Keywords: Acacia; alkalizer; calcium carbonate; granulation technique